2017
DOI: 10.1051/0004-6361/201630162
|View full text |Cite
|
Sign up to set email alerts
|

Kink oscillations of cooling coronal loops with variable cross-section

Abstract: We study kink waves and oscillations in a thin expanding magnetic tube in the presence of flow. The tube consists of a core region and a thin transitional region at the tube boundary. In this region the plasma density monotonically decreases from its value in the core region to the value outside the tube. Both the plasma density and velocity of background flow vary along the tube and in time. Using the multiscale expansions we derive the system of two equations describing the kink oscillations. When there is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 37 publications
5
47
0
Order By: Relevance
“…In the model applied here, we consider a loop of half-circular shape, where the curvature affects only the density distribution. The temperature is modelled to be exponentially decaying in time (similar to the profiles studied in, for example, Aschwanden and Terradas [2008]; Morton and Erdélyi [2010]; Ruderman [2011b]; Ruderman et al [2017]) and is approximated by:…”
Section: Theoretical Modelling and Observed Amplitude Profilesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the model applied here, we consider a loop of half-circular shape, where the curvature affects only the density distribution. The temperature is modelled to be exponentially decaying in time (similar to the profiles studied in, for example, Aschwanden and Terradas [2008]; Morton and Erdélyi [2010]; Ruderman [2011b]; Ruderman et al [2017]) and is approximated by:…”
Section: Theoretical Modelling and Observed Amplitude Profilesmentioning
confidence: 99%
“…where T0 is the constant external temperature and t cool is the cooling time (assumed to be the total lifetime of the oscillation here). Additionally, we describe the variation of the loop crosssection with height, z, in a manner similar to that discussed by Ruderman et al 2008Ruderman et al , 2017. This takes the form:…”
Section: Theoretical Modelling and Observed Amplitude Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Large amplitude kink waves have been shown to produce plasma flows along the field, and the ponderomotive force can cause accumulation of density at the loop top (e.g Terradas & Ofman 2004;Clack & Ballai 2009;Vasheghani Farahani et al 2012). The effect of a time-varying crosssection was recently investigated analytically in Ruderman et al (2017). In it was observed that the quality factor of kink oscillations decreases as the oscillation amplitude increases, indicating that finite amplitude effects are playing some role in modifying the damping time and/or period.…”
Section: Introductionmentioning
confidence: 99%